Implant-Free Subpectoral Biceps Tenodesis Is Biomechanically at Higher Risk of Spiral Fracture of the Humerus Compared With Implant-Free Suprapectoral Biceps Tenodesis - Arash A. Dini, M.D; Joshua E. Mizels, B.A; Sohale Sadeghpour, M.D; Michael J. O'Brien, M.D; Felix H. Savoie, III, M.D; Mark H. Getelman, M.D (Elsevier, 2021)
Purpose: To compare the likelihood of spiral fracture of the humerus using torsional load to failure after intraosseous biceps tenodesis at the position of the arthroscopic suprapectoral tenodesis versus the subpectoral meta-diaphyseal location. Methods: Eight matched pairs of humeri were dissected. Unicortical tenodesis holes were drilled, either at the bottom of the bicipital groove (group 1) or just below the pectoralis major tendon insertion (subpectoral) in the humeral diaphysis (group 2). Tenodesis was performed in a 7-mm bone tunnel, with suture fixation distal to this site using 2 separate 2-mm holes, secured with No. 2 polyester suture. Each humerus was potted in plaster and mounted to a hydraulic torsional load frame, consistent with previously validated models for creating humeral spiral fractures. External rotation torque was applied to each humerus distally until fracture occurred. The paired t test was used to compare the 2 groups. Results: Fracture occurred at the subpectoral cortical drill hole in all 8 specimens in group 2. In group 1, only 2 fractures occurred through the tenodesis hole, with spiral fracture resulting in the diaphysis of the humerus in 6 of 8 specimens. Average torque to failure measured 31.35 Nm in group 1 and 25.08 Nm in group 2; the difference was statistically significant (P < .0001). Conclusions: Subpectoral cortical drill holes for biceps tenodesis were shown to be a stress riser for humeral spiral fracture. Suprapectoral cortical drill holes were shown to be significantly less of a stress riser. The amount of torque required to fracture the humerus through the subpectoral drill holes was less than with the suprapectoral drill holes. Only 2 fractures occurred through the suprapectoral tenodesis holes, and significantly more torque was required to create these fractures. Clinical Relevance: Clinically, the difference between suprapectoral and subpectoral tenodesis fracture potential should be considered when selecting a tenodesis location.